Evaluating Benefits and Risks of Polyunsaturated Fatty Acids and Methyl Mercury from Fish and Seafood Consumption in Peninsular Malaysia - Nurul Izzah Ahmad; Noraishah Mohammad Sham (Journal of Food Quality)
The risks and benefits associated with methyl mercury (meHg) and polyunsaturated fatty acid (PUFA) from seafood consumption were assessed in adults and adolescents from Peninsular Malaysia. Seafood samples were collected for meHg analysis while the consumption survey was conducted among adults and pupils ≥10 years old. Long-chain omega-3 fatty acids (LC ω-3 PUFA; DHA and EPA) data were obtained from locally published articles. The estimated weekly intake (EWI), provisional tolerable weekly intakes (PTWIs), hazard quotient (HQ), and maximum safe weekly consumption (MSWC) were calculated for each seafood studied. The average range of LC ω-3 PUFA concentration was between 11.7 and 2,210.5 mg/100 g, where 27% of samples contained >500 mg/100 g and were predominant in pelagic fish and mollusks. MeHg concentrations in seafood samples ranged from 0.0426 to 0.4576 mg/kg of wet weight (WW) and showed significant variations between all species at a median concentration of 0.0621 ± 0.0573 mg/kg WW. Total seafood consumed by the adolescents was 84.7 ± 103.7 g/day, with significant marginal differences compared to the adult population at 90.5 ± 100 g/day. Long-tail tuna, yellow-stripe shad, slender shad, and long-tail shad contributed to a higher LC ω-3 PUFA intake than other species. These fish also contributed to a low HQ value level, lowering the risk of health effects. Mangrove red snapper has a low LC ω-3 PUFA content, but the HQ value was the highest of all, and it is advised to consume less frequently. Double the intake of cephalopod and a threefold increase in crustacean consumption would still minimize the meHg risk and may increase the intake of LC ω-3 PUFA.